Thermomechanical Behavior of Textile Reinforced Cementitious Composites Subjected to Fire - Panagiotis Kapsalis; Michael El Kadi; Jolien Vervloet; Matthias De Munck; Jan Wastiels; Thanasis Triantafillou; Tine Tysmans (Applied Sciences, 2019)
The mechanical behavior of textile reinforced cementitious composites (TRC) has been a topic of wide investigation during the past 30 years. However, most of the investigation is focused on the behavior under ambient temperatures, while only a few studies about the behavior under high temperatures have been conducted thus far. This paper focused on the thermomechanical behavior of TRC after exposure to fire and the residual capacity was examined. The parameters that were considered were the fiber material, the thickness of the concrete cover, the moisture content and the temperature of exposure. The specimens were exposed to fire only from one side and the residual strength was measured by means of flexural capacity. The results showed that the critical factor that affects the residual strength was the coating of the textiles and the law of the coating mass loss with respect to temperature. The effect of the other parameters was not quantified. The degradation of the compressive strength of TRC was quantified with respect to temperature. It was also concluded that a highly asymmetrical design scheme might lead to premature failure.